PENGARUH CORPORATE SOCIAL RESPONSIBILITY, UKURAN PERUSAHAAN, DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR SUBSEKTOR FOOD & BEVERAGE PERIODE 2021-2023 - Ni Putu Kesumayanti; Luh Gede Pande Sri Eka Jayanti; I Gusti Ayu Intan Saputra Rini (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Warmadewa, 2025)
This study aims to analyze the impact of CSR, company size, and profitability on the value of companies in the food and beverage manufacturing sector listed on the Indonesian Stock Exchange from 2021 to 2023. This study employs a quantitative approach. Data collection is carried out using the purposive sample method, with a total population of approximately 95 food and beverage companies that were present throughout the relevant period, 24 of which satisfied the predetermined criteria. The secondary data used in this study is derived from the official Bursa Efek Indonesia website at www.idx.co.id. Analysis is conducted using the Linear Berganda Regression, and to ensure the accuracy of the analysis, a klasik assumption is made as a pre-regression test, followed by a model evaluation (uji F), a hypothesis test (uji t), and a determination of the coefficient of determination (R²). The findings of this study indicate that while corporate social responsibility has a positive impact on a company's value, a company's size has a negative impact, and profitability does not have a negative impact on a company's value.